2010
DOI: 10.1007/s12281-010-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

Sporotrichosis Treatment: Overview and Update

Abstract: Sporotrichosis, caused by several species from the genus Sporothrix, mainly affects men working in agricultural labor. It is reported mostly from endemic regions located in tropical and subtropical areas. Sporotrichosis usually affects subcutaneous tissue with no symptoms or mild symptoms, but it causes disseminated and even fatal disease if the patient is immunocompromised. Significant progress in the knowledge of etiologic agents of sporotrichosis has been achieved recently, but evaluations of treatment usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
1
0
0
4
Order By: Relevance
“…Although PLHIV had more severe diseases, their cure rate did not differ from patients without HIV infection. This reinforces the severity of the disease and the limits of AMB in severe sporotrichosis treatment [ 41 ]. One explanation for this limitation is that in vitro studies demonstrated good susceptibility of S. brasiliensis to oral antifungals, such as itraconazole, posaconazole, and terbinafine, in contrast to the moderate efficacy of AMB [ 38 , 40 ].…”
Section: Discussionsupporting
confidence: 62%
“…Although PLHIV had more severe diseases, their cure rate did not differ from patients without HIV infection. This reinforces the severity of the disease and the limits of AMB in severe sporotrichosis treatment [ 41 ]. One explanation for this limitation is that in vitro studies demonstrated good susceptibility of S. brasiliensis to oral antifungals, such as itraconazole, posaconazole, and terbinafine, in contrast to the moderate efficacy of AMB [ 38 , 40 ].…”
Section: Discussionsupporting
confidence: 62%
“…Na América Latina, o tratamento de escolha para as formas cutâneas da doença é a solução saturada de iodeto de potássio, pela sua eficácia conhecida e custo acessível. 8 Embora haja recomendações internacionais para o itraconazol como primeira linha de tratamento, há evidencia de eficácia semelhante à solução saturada de iodeto de potássio. A solução saturada de iodeto de potássio é mais facilmente administrada e aceite pelas crianças 5 e nesta faixa etária não existem habitualmente contraindicações para a sua utilização.…”
Section: Discussionunclassified
“…Sin embargo, en los países de América Latina es ampliamente utilizado el yoduro de potasio (KI) para estas formas cutáneas, formulándolo a una concentración de 1g/mL y se administra a una dosis de 3 a 6 g/día, dividido en tres dosis por tres a cuatro meses aproximadamente, hasta la resolución de las lesiones y mantener de dos a cuatro semanas más; con este esquema se han reportado tasas de curación de 89 a 100%, con un nivel de evidencia II-A. 3,[9][10][11][12][13][14][15] En caso de persistencia de las lesiones o cuando hay contraindicaciones, la criocirugía es una opción, ya que el hongo es sensible a temperaturas extremas. 10 Un estudio sobre el tratamiento de la esporotricosis en humanos que utilizan nitrógeno líquido arrojó buenos resultados.…”
Section: Wwwmedigraphicorgmxunclassified